1977
DOI: 10.1007/bf01314662
|View full text |Cite
|
Sign up to set email alerts
|

IgM antibodies to cytomegalovirus during pregnancy

Abstract: IgM antibodies to cytomegalovirus (CMV) could be detected in about 7 per cent of 629 pregnant women whereas in 225 nonpregnant control women of similar age distribution only 2.6 per cent showed CMV IgM antibodies. Intrauterine CMV infections were almost exclusively detected among the CMV IgM positive gravides. The high incidence of CMV IgM antibodies in pregnant women can be possibly explained by an increased rate of CMV reactivations during pregnancy. We were able to show that during CMV reactivation an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

1977
1977
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…For example, it is known that CMV is activated during pregnancy [Schmitz et al, 1977] and this was also considered for HPV [Chang-Claude et al, 1996;Smith et al, 1991]. This would agree with the finding that the prevalence of AAV IgG antibodies is much higher in pregnant women compared to women of the same age group.…”
Section: Discussionsupporting
confidence: 82%
“…For example, it is known that CMV is activated during pregnancy [Schmitz et al, 1977] and this was also considered for HPV [Chang-Claude et al, 1996;Smith et al, 1991]. This would agree with the finding that the prevalence of AAV IgG antibodies is much higher in pregnant women compared to women of the same age group.…”
Section: Discussionsupporting
confidence: 82%
“…titre in the third trimester. Schmitz et al (1977) in Freiburg using the fluorescence technique found specific IgM in 7 % of the 629 patients studied by them, a rate higher than that found by us. They explain this high incidence by an increased rate of CMV reactivations during pregnancy.…”
Section: Discussioncontrasting
confidence: 67%
“…Data on the elinicM significance of either primary or recurrent infections have been accumulated during prospective studies where the immune response could be tested prior to onset of an acute CMV infection. In these studies a close correlation was found between primary CMV infections and severe clinical symptoms including rnMformations in pregnancy (3,9,13,14). However, with most CMV patients serum specimens are only available during the first or second week after the onset of symptoms and seroconversions are rarely observed.…”
Section: Introductionmentioning
confidence: 82%
“…Two sera obtained from two pregnant women after seroeonversion to CMV during pregnancy (9) were also included in this study.…”
Section: Patients and Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation